Uncertainty Principles and Extremal Functions for the Dunkl L2-Multiplier Operators. (14th August 2014) - Soltani, Fethi
Abstract : We study some class of DunklL 2 -multiplier operators; and related to these operators we establish the Heisenberg-Pauli-Weyl uncertainty principle and Donoho-Stark's uncertainty principle. We give also an application of the theory of reproducing kernels to the Tikhonov regularization on the Sobolev-Dunkl spaces.